Differential familial liability of panic disorder and agoraphobia - Nocon, A.; Wittchen, H.-U.; Beesdo, K.; Brückl, T.; Hofler, M.; Pfister, H.; Zimmermann, P.; Lieb, R. (Depression and anxiety, 2008)
To examine the familial liability of panic disorder (PD) and agoraphobia (AG) in a community sample, namely the effect of parental PD and AG on the offspring's risk to develop either or both conditions in adolescence or adulthood. A representative community sample of N=3,021 adolescents and young adults aged 14–24 years at baseline was followed up over a period of 10 years in up to four waves. Family information was assessed by either direct interviews with at least one parent or by using subjects' family history information at either wave (N=3,014). Diagnoses and selected symptoms were assessed in both, parents and subjects, by using a standardized diagnostic interview (DSM‐IV M‐CIDI) with its respective family history module. (1) Parental panic attacks (PA), PD, and AG were all shown to be associated with an increased risk of offspring to also develop PA, PD, and AG. (2) Associations of parental PD were present irrespective of parental AG, whereas parental AG without PD was not associated with an increased offspring risk. (3) Outcome risk was particularly elevated in offspring of parents with PD+AG. (4) Parental PD or AG was not associated with an earlier age of onset of any syndrome in the offspring. We confirmed and expanded previous results from clinical samples that comorbid PD and AG aggregate in families. AG without PD is not familial, but it might enhance the familial transmission of PD. Depression and Anxiety 0:1–13, 2007. © 2007 Wiley‐Liss, Inc.